DINAMIKA PERAN DAN CYBERLOAFING - Nanny Nydia; Fahrudin Js Pareke (Management Insight: Jurnal Ilmiah Manajemen, 2019)
The existence of the internet can help activities in running a company, and it is very useful for improving internal and external communication, and also able to strive for more efficient services. So that internet usage has become an unavoidable need. However, it is still much more employees use the internet that has nothing to do with work, called cyberloafing behavior. The current study intend to investigate the dynamic of employee’s role in the work place, such as role conflict, role ambiguity, role ove rload, and its relation to the cyberloafing. The goal of the research is to test the effect of role conflict, role ambiguity, and role overload on cyberloafing. Eighty employees from a private company located in Bengkulu city choosen as sample frame of the research. The Multiple Regression Analysis was employed to test theresearch hypotheses. The research conluded that role conflict and role ambiguity affect the cyberloafing behavior positively, while the role overload affect the cyberloafing behavior negatively